Chloride‐Ion‐Stabilized Strontium Mayenite: Expansion of Versatile Material Family. Issue 12 (22nd August 2014) - Dong, Yingchao; Hayashi, Katsuro; Nozoe, Hiroki; Shinoda, Yutaka; Hosono, Hideo; Vanderah, T.
<x xml:space="preserve">Abstract</x> Sr‐mayenite (S12A7) incorporating Cl− ions in its crystallographic cages up to the theoretical maximum occupancy, Sr12Al14O32Cl2, is reported in our study. The addition of a stoichiometric amount of SrCl2 to the starting mixture is effective for the formation of Sr12Al14O32Cl2 with high phase purity. Almost 100% densification is achieved using spark plasma sintering (SPS). Evaporation of SrCl2 from Sr12Al14O32Cl2, which becomes significant at sintering temperatures above ~1300°C, degrades the phase purity. However, SrCl2 effusion is significantly suppressed in the samples fully densified by SPS, impeding the decomposition of Sr12Al14O32Cl2 up to temperature as high as ~1400°C. The crystal structure of Sr12Al14O32Cl2 was investigated by Rietveld analysis of the X‐ray diffraction pattern. It is found that the Cl− ion is incorporated in the center of the inner cage with nearly theoretical maximum occupancy, which is responsible for the phase stability. Porous Sr12Al14O32Cl2 exhibits humidity‐sensitive surface protonic conductivity. Dense Sr12Al14O32Cl2 prepared under reducing conditions such as SPS exhibits electronic conductivity. Sr‐mayenite has various potential applications derived from its multifunctionalities.